2021
DOI: 10.29303/jppipa.v7ispecialissue.1083
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Practicality of Guided Inquiry-Based E-Modules accompanied by Virtual Laboratory to Empower Critical Thinking Skills

Abstract: This study aims to determine the validity and practicality of guided inquiry-based e-modules accompanied by virtual laboratories on digestive system materials to empower critical thinking skills. The type of research used is research and development (R&D), by applying the Borg and Gall development model consisting of 10 steps and grouped in four stages including: preliminary study stage, development, testing, and deployment. This study is limited to e-modules validity and practicality testing. The instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…Dosen juga jarang mengoptimalkan ketersediaan aplikasi virtual laboratory untuk mengoptimalkan pembelajaran eksperimen atau penyelidikan sehingga pembelajaran menjadi serba terbatas. Hal ini sejalan dengan penelitian Ravista, et al (Ravista, 2021) yaitu ada hal terkait proses pembelajaran: 1) Pendidik memiliki beberapa metode pembelajaran seperti ceramah dan diskusi tapi belum menggunakan model pembelajaran inovatif; 2) Pendidik jarang menjalankan kegiatan eksperimen; 3) Materi pembelajaran masih konvensional atau menggunakan bahn cetak (print), yaitu materi yang ditampilkan beum memfasilitasi siswa untuk melakukan aktivitas discovery dan melatih melakukan kegiatan saintifik.…”
Section: Hasil Dan Pembahasan Studi Pendahuluanunclassified
See 1 more Smart Citation
“…Dosen juga jarang mengoptimalkan ketersediaan aplikasi virtual laboratory untuk mengoptimalkan pembelajaran eksperimen atau penyelidikan sehingga pembelajaran menjadi serba terbatas. Hal ini sejalan dengan penelitian Ravista, et al (Ravista, 2021) yaitu ada hal terkait proses pembelajaran: 1) Pendidik memiliki beberapa metode pembelajaran seperti ceramah dan diskusi tapi belum menggunakan model pembelajaran inovatif; 2) Pendidik jarang menjalankan kegiatan eksperimen; 3) Materi pembelajaran masih konvensional atau menggunakan bahn cetak (print), yaitu materi yang ditampilkan beum memfasilitasi siswa untuk melakukan aktivitas discovery dan melatih melakukan kegiatan saintifik.…”
Section: Hasil Dan Pembahasan Studi Pendahuluanunclassified
“…Kelayakan pada aspek penyajian memperoleh skor 87%. Ini membuktikan bahwa LKPD digital terdiri dari komponen lengkap untuk memfasilitasi keterlibatan siswa dalam proses belajar (Ravista, 2021).…”
Section: Gambar 1 Tampilan Depan Lkpd Digital Berbasis Simulasi Phetunclassified
“…Innovative, contextual, and interesting teaching materials will enable students to learn more effectively and develop higher levels of thinking (Suryawati & Osman, 2018). Providing effective teaching materials is an essential component of the learning process (Ravista et al, 2021). One type of teaching material that contains a set of planned, whole, and systematic learning experiences to help students master specific learning competencies is a module (Harahap & Fauzi, 2017;Resita & Ertikanto, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Brown (2010) reported that the POGIL (Processoriented guided-inquiry learning) learning model was able to empower students' critical thinking in studying biology through a series of questions. Ravista et al (2021) also reported that the use of an electronic module based on an inquiry strategy accompanied by a virtual laboratory could improve students' critical thinking in learning biology. Inquiry strategies could also improve biology learning outcomes through a series of combinations of techniques or methods and modifications.…”
Section: Introductionmentioning
confidence: 99%